2022
DOI: 10.3389/fmicb.2022.892767
|View full text |Cite
|
Sign up to set email alerts
|

16S rRNA Gene Sequencing Reveals Specific Gut Microbes Common to Medicinal Insects

Abstract: Insects have a long history of being used in medicine, with clear primary and secondary functions and less side effects, and the study and exploitation of medicinal insects have received increasing attention. Insects gut microbiota and their metabolites play an important role in protecting the hosts from other potentially harmful microbes, providing nutrients, promoting digestion and degradation, and regulating growth and metabolism of the hosts. However, there are still few studies linking the medicinal value… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 130 publications
0
3
0
Order By: Relevance
“…Numerous studies have demonstrated that gut bacteria have various impacts on insect physiology [ 23 ]. However, although many microbial communities in the alimentary canals of insects have been described, there is currently limited research on vectors, especially Steganinae, in which some species act as vectors of T. callipaeda .…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have demonstrated that gut bacteria have various impacts on insect physiology [ 23 ]. However, although many microbial communities in the alimentary canals of insects have been described, there is currently limited research on vectors, especially Steganinae, in which some species act as vectors of T. callipaeda .…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have demonstrated that gut bacteria exhibit varied impacts on insect physiology [23].…”
Section: Discussionmentioning
confidence: 99%
“…The distance-based redundancy analysis was performed using Vegan v2.5-3 package to investigate effect of silage characteristic on silage bacterial community. A random-forest classification was conducted by using R packet random Forest 4.6-14 84 . According to the previous method 85 , 86 , microbial co-occurrence networks were built by using CoNet module of Cytoscape 3.9.1 and were viewed in Gephi software.…”
Section: Methodsmentioning
confidence: 99%